Interactive video learning approach for English vocabulary learning / Siti Norakmal Md Ariffin - Md Ariffin, Siti Norakmal (2017)
The attempt to produce this research is to clarify whether the interactive video can assist the student in learning English vocabulary. Interactive video is the video that can interact with the user, where when the user makes a selection, the video can give a fast response to the user. Therefore, the interactive video has been introduced to assists students in learning English vocabulary because English is a very important language and vocabulary plays an important part in the English language where without vocabulary the sentences are meaningless. This research compares the effectiveness of the interactive video and conventional approach that currently being used. Either it can assist the student in the rural area in learning English vocabulary in interactive way of learning. Inspired by the teaching processes in school the interactive video is using lots of pictures and sounds to assist students in learning vocabulary. The interactive video presented by combining sounds and picture that will show a short story. This approached will act as an additional tool to assist respondents studying in Form 1 secondary school to improve their English vocabulary using interactive video. With the help from the interactive video, the student will be able to learn on their own with minimum assistance from the teacher. The school involved two states which are Kelantan and Selangor. 50 students of Form 1, was selected from two secondary schools. The pre-test, post-test, and t-test are the evaluation process to gather the feedback from the respondents. From the evaluation results, it does have proven that the interactive video did improve the students' performance. The limitations and directions for future development and research are discussed accordingly.